Conselhos tutelares e a defesa do direito de crianças e adolescentes à convivência familiar e comunitária: uma anaise do município de João Pessoa PB. - Ribeiro, Thayse Carla Barbosa (2011)
This study intends to analyze the activity of the Conselhos Tutelares (Tutelary Councils) in João Pessoa, PB, with focus on the defense of the right to familiar and communitarian acquaintanceship - which lies in the primary rights for children and adolescents in the Federal Constitution of Brazil (1988) and also in the Estatuto da Criança e do Adolescente (Statute for Children and Adolescents). Essentially based on qualitative data (quantitative data appear just to enlighten the analysis), the research outlines the study of cases which can be seen by a dialectic method and which elected as categories the democratic participation (giving emphasis to Tutelary Councils as places for its effectuation), the communitarian and familiar acquaintanceship as a right for children and adolescents (focusing on its characteristics nowadays and its role as a social protection agent). The research has as subject all the Tutelary Councils in João Pessoa, PB. The statistics were collected by means of questions, semi-structured interviews and documental analysis (legal processes of 2009 in which we found some material about the right to communitarian and familiar acquaintanceship); besides, the analysis of contents was used during the interpretation of the mentioned data. In synthesis, the results appoints that children and adolescents remain being taken from their families to tutelary councils due to their poverty, in spite of its legal prohibition fact related to the ineffectiveness of the public and social politics even the Brazilian Federal Law 12.010/09 stating, in general, some kind of warning about the deliberate use of institutional reception. By the way, it has been seen that Tutelary Councils act in an individualized way, privileging its own assistential part in order to elaborating attendances and referrals instead of trying to solve problems in the public environment. This situation contributes (between other eventual problems) to its own fragility as mechanism to assure children and adolescents rights, although it has potential to such an act.